Defect induced improved capacitive performance of MnS incorporated MoO3 nanocomposite for supercapacitor electrodes in aqueous electrolytes - Mizanur Rahaman; Mehedi Hasan Prince; Saif Mahmud Bijoy; Zakaria Siddiquee; Muhammad Rakibul Islam (PLoS ONE, 2026)
Electrode materials play a crucial role in improving supercapacitor performance. In this work, MnS nanoparticles were incorporated into MoO 3 to form a MoO 3 /MnS nanocomposite via hydrothermal synthesis, and the capacitive performance of the resulting supercapacitor electrodes was evaluated. Their electrochemical performances were studied in conjunction with KCl and Na 2 SO 4 electrolytes. The generation of MoO 3 /MnS nanocomposite was confirmed by XRD analysis and HR-TEM imaging. It is found that the MnS nanoparticles altered the morphology of MoO 3 from nanobelts to nanofibers and produced a defective, rough surface. The defective surface expanded the interlayer distance from 0.396 nm to 0.421 nm. In both ionic electrolytes, the MoO 3 /MnS composite demonstrated higher capacitive performance than the pristine MoO 3 . At 0.3 A g -1 current density, the estimated specific capacitance of MoO 3 /MnS was 387 F g -1 and 335 F g -1 in KCl and Na 2 SO 4 electrolytes, respectively. In the symmetric two-electrode system, the MoO 3 /MnS shows a specific capacitance of 297 F g −1 at 1 A g −1 , with an energy density of 33.37 Wh kg −1 and a power density of 450 W kg −1 . The MoO 3 /MnS nanocomposite provides excellent 90% retention after 1000 continuous charging-discharging cyclic. The enhancement of electrochemical performance is attributed to the large surface area, defective morphology, and broader interlayer distance. This system bridges the gap between traditional batteries and capacitors, offering a unique approach to producing supercapacitor electrodes.